Q: What is 4t plus 3s plus 2p equals c?

Write your answer...

3s + 4t + 2s + 5s + 6tGroup all of the like 's' terms & 't' terms together:(3s+2s+5s) + (4t + 6t)10s + 10t or 10(s+t)

4t - 2p

If 4t + 5 = 37, then t = 8.

9t = 4t + 120 9t-4t = 4t - 4t + 120 5t = 120 5t/5 = 120/5 t = 24 24 is your answer

2

It is an equation and the value of t is 1

NEVERMIND!

T+(3-2t)=4t+1. Assuming the two T's , T and t are the same variable, lets proceed. t+(3-2t)=4t+1 3-t=4t+1 2-t=4t 2=5t last step is yours

t in this problem equals -3. 4t- 8+ 25= 5 -25 -25 4t- 8= -20 +8 +8 4t= -12 /4 /4 t= -3

4t-1 = t+2 3t -1 = 2 3t = 3 t = 1

4t + 13t + 2 = 17t + 2

4t = 24 Therefore t = 24/4 t = 6

t + 10 - 4t = -11 Subtract 10 from each side: t - 4t = -21 ie -3t = -21 t = -21/-3 t = 7.

4t - 3 = 19 4t = 19 +3 = 22 t = 22/4 t = 5.5

4T

You don't have enough information to solve this. You need to know what P is, or what T is, otherwise you can't get an answer.

4t +7

-2t = -10

8,000 lbs

-4t+5t-8+4=6t-4 eqn soln t=0 transpose variable terms on one side & constant terms on the other side of equality

7s + 4t

4t - 6 = 4*(-6) -6 = -24 -6 = -30

10t=6t+24 -6 -6 4t=24 4 4 1=6 t=6

8625lb

T(t + 4)